ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PERUSAHAAN BUMN SEKTOR KONSTRUKSI YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Zeze Zakaria Hamzah; Tyara Pratiwi Poernomoputri; Muchammad Hamdani; Siti Adawwiah (Institut Teknologi dan Bisnis Dewantara, 2025)
This research aims to find out and analyze the company’s financial performance of BUMN companies in the construction sector listed on the IDX for the 2018-2021 period based on financial ratios, supported by vertical and horizontal analysis. The method used in this research is quantitative research. The results of the research show that: 1) Based on the ratio analysis, CR results ranked 1st is WIKA, Followed by PTPP, ADHI, and WSKT. NPM results ranked 1st is WIKA, followed by PTPP, ADHI, and WSKT. DAR results ranked 1st is PTPP, followed by WIKA, WSKT, and ADHI. TATO results ranked 1st is ADHI, followed by PTPP, WIKA, and WSKT. 2) Based on the vertical analysis on the statement of financial position, ranked 1st is ADHI, followed by WIKA, PTPP, and WSKT. While based on the vertical analysis on the income statement, ranked 1st is WIKA, followed by PTPP, ADHI and WSKT. 3) Based on the horizontal analysis on the statement of financial position, ranked 1st is ADHI, followed by WIKA, PTPP, and WSKT. While based on the horizontal analysis on the income statement, ranked 1st is ADHI, followed by WWIKA, PTPP, and WSKT.